Natural fish oil improves the differentiation and maturation of oligodendrocyte precursor cells to oligodendrocytes in vitro after interaction with the blood–brain barrier - Piatek, Paweł; Lewkowicz, Natalia; Michlewska, Sylwia; Wieczorek, Marek; Bonikowski, Radosław; Parchem, Karol; Lewkowicz, Przemysław; Namiecinska, Magdalena (Frontiers in Immunology, 2022)
The blood-brain barrier (BBB) tightly controls the microenvironment of central nervous system (CNS) to allow neurons to function properly. Additionally, emerging studies point for beneficial effect of natural oils affecting a wide variety of physiological and pathological processes in the human body. In this study, using in vitro model of BBB, we tested the influence of natural fish oil mixture (FOM) vs. borage oil (BO), both rich in PUFAs, NA and SFAs on human oligodendrocyte precursor cells (hOPCs) during their maturation to oligodendrocytes (OLs) with their ability to myelin peptide and NA synthesis. We demonstrated that FOM, opposite to BO, supplemented endothelial cells (ECs) and astrocytes forming BBB, affecting the function of hOPCs during their maturation. This resulted in the improved synthesis of myelin basic proteins (MBP), myelin oligodendrocyte glycoprotein (MOG), proteolipid protein (PLP) as well as NA synthesis in mature OLs. This effect is probably the result of BBB cell and hOPC stimulation via free FA receptors (FFARs), which increases IGF-1, CTNF, BDNF and inhibits FGF-2 synthesis. The unique formula of fish oil, characterized by much more varied components compared to borage oils, also improved enhancement of tight junction by increasing expression of Claudin-5 and VE-cadherin on ECs. The obtained data justify consideration of natural derived fish oil intake in human diet especially during remyelination.